The Interaction Between Religion and Science in Catholic Southern Europe (Italy, Spain, Portugal) - Oviedo Torró, Lluís (Zygon, 2015)
Reviewing the last fifty years of interaction between religion and science in Catholicism in Southern Europe, common traits are clearly evident: a late awareness of the importance of this interaction and a theological reluctance to address science or to account for its progress. Early signs of the engagement between religion and science appear as a consequence of the work of the French anthropologist and theologian Teilhard de Chardin. In Italy and Spain in the last fifteen years, we see a substantive growth in the rise of research centers and academic activities devoted to exploring the common ground between science, philosophy, and theology. However, despite all these efforts and the many positive signs, there remains a long way to go for theology to consider science as a true challenge and an inspiration and to integrate it into the theological curriculum.